"Critical feminist justpeace": a grounded theory approach to Women, Peace and Security. Issue 5 (20th October 2022) - Riddle, Karie Cross
ABSTRACT: More than 20 years after the landmark achievement of the Women, Peace and Security (WPS) agenda, feminist scholars and activists are debating the conditions in which peacebuilders should employ the agenda and those in which they should pursue alternatives. This article argues that the conflict and peacebuilding in Manipur, a state in Northeast India, is ripe for creative thinking beyond WPS. India refuses to acknowledge legally this intractable, low-intensity armed conflict, barring international and humanitarian actors from entry. Moreover, the WPS agenda has failed to reach from New Delhi into the marginalized Northeast region, where plentiful forms of direct and structural violence persist. Thus, rather than rallying around the WPS agenda for this case, feminist scholars and activists should find other ways to support longstanding women's peacebuilding initiatives. Using Ackerly's critical feminist methodology, I synthesize inductive insights from women's peacebuilding praxis and apply them to Lederach's contextual and relational approach to conflict transformation, revising it to incorporate the gendered concerns of women building peace across ethnic and religious differences. The result is a grounded normative theory called "critical feminist justpeace, " an alternative to the WPS approach.